Energy‐optimal coverage path planning on topographic map for environment survey with unmanned aerial vehicles. Issue 9 (11th April 2016) - Li, Deshi; Wang, Xiaoliang; Sun, Tao
Abstract : An energy‐optimal coverage path planning algorithm is proposed for environment survey. First, 3D terrains are modelled by tensor product Bezier surfaces for a mesh representation. Then, a power estimator is derived to calculate the consumed energy for a piecewise spatial path. Based on the digital surface model, an energy consumption map is constructed for the whole area by means of a weighted directed graph. Finally, an energy‐optimal path can be achieved through traversing the map by a genetic algorithm. Numerical experiments demonstrate the effectiveness and efficiency of the proposed algorithm.